1990
DOI: 10.1126/science.1699275
|View full text |Cite
|
Sign up to set email alerts
|

Flip and Flop: A Cell-Specific Functional Switch in Glutamate-Operated Channels of the CNS

Abstract: In the central nervous system (CNS), the principal mediators of fast synaptic excitatory neurotransmission are L-glutamate-gated ion channels that are responsive to the glutamate agonist alpha-amino-3-hydroxy-5-methyl-4-isoxazole propionic acid (AMPA). In each member of a family of four abundant AMPA receptors, a small segment preceding the predicted fourth transmembrane region has been shown to exist in two versions with different amino acid sequences. These modules, designated "flip" and "flop," are encoded … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

24
655
0
15

Year Published

1995
1995
2017
2017

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 1,183 publications
(694 citation statements)
references
References 41 publications
(6 reference statements)
24
655
0
15
Order By: Relevance
“…While this would seem to implicate a KAreceptor subtype, one cannot be confident in this conclusion for the following reasons: (1) AMPA and KA receptor ligands show a very high degree of receptor cross-reactivity; (2) when AMPA or KA are applied continuously to AMPA-preferring receptors, a desensitization mechanism is triggered in response to AMPA but not to KA. 49,50 For further clarification, we used cyclothiazide, an agent that is known to prevent AMPA receptor desensitization. Consistent with a role for an AMPA preferring receptor, we found that the addition of cyclothiazide to the carbachol+AMPA cocktail allowed the neurotoxic reaction to be expressed.…”
Section: Discussionmentioning
confidence: 99%
“…While this would seem to implicate a KAreceptor subtype, one cannot be confident in this conclusion for the following reasons: (1) AMPA and KA receptor ligands show a very high degree of receptor cross-reactivity; (2) when AMPA or KA are applied continuously to AMPA-preferring receptors, a desensitization mechanism is triggered in response to AMPA but not to KA. 49,50 For further clarification, we used cyclothiazide, an agent that is known to prevent AMPA receptor desensitization. Consistent with a role for an AMPA preferring receptor, we found that the addition of cyclothiazide to the carbachol+AMPA cocktail allowed the neurotoxic reaction to be expressed.…”
Section: Discussionmentioning
confidence: 99%
“…A switch in the molecular and functional properties of glutamate receptors operates by alternative splicing (Fig. 6a) (Sommer et al 1990). The spliced pattern of the GluR-B gene was analysed by RT-PCR (Fig.…”
Section: Nssr 1 Promotes the Inclusion Of The Flip Exon In Glur-b Andmentioning
confidence: 99%
“…Despite these relatively few reported cases, mutually exclusive splicing might be far more frequent in humans than currently anticipated, as has been recently revealed in the model organism Drosophila melanogaster (Hatje & Kollmar, 2013). Apart from their low number, MXEs have been described in many crucial and essential human genes such as in the α‐subunits of six of the 10 voltage‐gated sodium channels ( SCN genes) (Copley, 2004), in each of the glutamate receptor subunits 1–4 ( GluR1‐4 ) where the MXEs are called flip and flop (Sommer et al , 1990), and in SNAP‐25 as part of the neuroexocytosis machinery (Johansson et al , 2008). Although MXEs within a cluster often share high similarity at the sequence level, they are usually not functionally redundant, as their inclusion in the mRNAs is tightly regulated.…”
Section: Introductionmentioning
confidence: 99%